Development of a nested PCR assay for detecting Colletotrichum siamense and Colletotrichum fructicola on symptomless strawberry plants. - Pei-Che Chung; Hung-Yi Wu; Yi-Chia Chen; Ting-Hsuan Hung; Chia-Lin Chung (PLoS ONE)
Anthracnose is a major disease of strawberry that seriously impacts the strawberry industry. To prevent the spread of anthracnose through symptomless plants, it is important to detect pathogenic Colletotrichum spp. at the latent infection stage in the nursery. Previous PCR-based methods developed for the diagnosis or detection of Colletotrichum acutatum and Colletotrichum gloeosporioides have used primers targeting the internal transcribed spacer region of ribosomal DNA, β-tubulin gene, or mating type gene. In this study, to specifically detect Colletotrichum siamense and Colletotrichum fructicola, the most predominant and virulent Colletotrichum species causing strawberry anthracnose in Taiwan, we conducted a comparative genomics analysis of 29 Colletotrichum spp. and identified a non-conserved 1157-bp intergenic region suitable for designing specific primers for a nested PCR assay. In silico analysis and actual tests suggested that the new nested PCR assay could detect pathogenic C. siamense and C. fructicola, but not other strawberry pathogens (Botrytis sp., Fusarium spp., Neopestalotiopsis rosae, and Phytophthora sp.) or ubiquitous saprophytes (Fusarium spp. and Trichoderma spp.). The inner to outer primer ratio was optimized to 1:10 to eliminate unexpected bands and enhance the signal. The assay could detect as little as 1 pg of C. siamense genomic DNA, which corresponds to ~15 cells. Application of the new detection assay on 747 leaf samples collected from 18 strawberry nurseries in 2019 and 2020 showed that an average of 20% of strawberry mother plants in Taiwan were latently infected by C. siamense or C. fructicola. The newly developed assay is being applied to facilitate the production of healthy strawberry runner plants in Taiwan.